Enhanced electrostatic AChE activity of abnormally hydrophobic environment in Alzheimer's plaques - Sharma, Rakesh (Informatica Medica Slovenica, 2008)
Computational techniques based on Brownian dynamics simulation speculate the electrostatic and kinetic properties of Acetylcholinesterase (AChE) in the range of dielectric constant values 60-78. Typically the enzyme specific to Alzheimerćs Disease has specificity constant (kcat/Km) of AChE at both dielectrics constants. AChE is distributed heterogeneously within the senile plaques and neurofibrillary tangles (NFTs) of Alzheimerćs Disease (AD). The role of decreased brain AChE has been highlighted as responsible for specific Magnetic Resonance Spectroscopic pattern profiles in AD. These findings strengthen the suggestion that the altered AChE in AD may be associated with specific MR spectral peak patterns. This phenomenon may account for the reduced levels of the ACh neurotransmitter in the cerebral tissue of Alzheimerćs disease (AD) patients. These results can be useful in clinical trials on AD lesions.
Keywords: Acetilholinesteraza; Acetylcholinesterase; Alzheimerjeva bolezen; Alzheimer'S Disease; Amiloidna beta-beljakovina; Amyloid Beta-Protein; diagnostika; Diffusion; Difuzija; Electrostatics; Elektrostatika; jedrna magnetna resonanca; Magnetic Resonance Imaging; Magnetna resonanca slikovna; Osmolar Concentration; Osmolarna koncentracija; Torpedo